Influence of MLC901 Alone and with Moderate Exercise on Pain Response Concurrent Due to Stress of Male Mice: - Nasehi, Maryam; Ghazalian, Farshad; Shakeri, Nader; Nasehi, Mohammad; Zarrindast, Mohammad-Reza (Galen Medical Journal, 2019)
Background: Physical exercise is known to have a positive effect on pain responses induced by stress, while chronic stress causes a negative effect on cognitive abilities. Depending on the type, duration, and intensity of the stressor, it can induce analgesia or hyperalgesia. Furthermore, the beneficial effects of traditional Chinese medicine MLC901 on stress processes have been reported. Here, the effects of MLC901 and moderate physical activity on pain response in restraint-stressed mice was investigated. Materials and Methods: Male NMRI mice were used in this study and were restrained in plexiglass mesh restrainers for induction of chronic restraint stress. Treadmill exercise was carried out for moderated exercise, 5 days/week for 4 weeks. MLC901 was intraperitoneally administered in the experimental groups. The pain response of the adult NMRI mice was detected via the hot-plate test. Results: It was showed that intraperitoneal administration of MLC901 dose (0.4 but not 0.1 and 0.2 mg/kg; once/2 days; for 25 days) resulted in the decreased percentage of time in the hot plate, indicating hyperalgesia. Moreover, restraint stress for 3 but not 6 and 9 hours/day elicit hyperalgesia in mice. The data showed that subthreshold dose of MLC901 (0.1 mg/kg) reduced hyperalgesia in 3-day stressed mice. Moderate treadmill running (10 meters/min for 30 min/day, 5 days/week) potentiated the effect of 6 and 9 days on pain (induced hyperalgesia) that was blocked by MLC901 (0.1 mg/kg). Conclusion: Our findings indicated that subthreshold dose of MLC901 alone or when it associated with moderate exercise decreased hyperalgesia induced by stress, indicating the protective effect of MLC901. [GMJ.2019;8:e1253]